Comparison of 3 Intensities of Stimulation Threshold for Brachial Plexus Blocks at the Midhumeral Level: A Prospective, Double-Blind, Randomized Study. Issue 4 (1st June 2009) - Cuvillon, Philippe; Dion, Nicolas; Deleuze, Michel; Nouvellon, Emmanuel; Mahamat, Aba; L'Hermite, Joel; Boisson, Christophe; Vialles, Nathalie; Ripart, Jacques; de La Coussaye, Jean Emmanuel
Abstract : Background: We conducted this prospective randomized study to compare the success rate and the onset time between 3 intensities of stimulation threshold (<0.5, 0.5-0.64, and 0.65-0.8 mA) when using a peripheral nerve stimulation at the midhumeral level. Methods: Sixty-nine adult patients undergoing elective hand surgery were studied. Blocks were performed using conventional nerve stimulation technique. Needle advance began at 2 mA (1 Hz, 0.1 millisecond). When motor response (MR) occurred at less than 0.5 mA, needle position was fixed for "group <0.5 mA." For "group 0.5-0.64 mA, " the needle was withdrawn until MR occurred at greater than 0.5 mA and disappeared at less than 0.5 mA. For "group >0.65 mA, " the needle was withdrawn until MR occurred at greater than 0.65 mA and disappeared at less than 0.65 mA. For each group, patients received 8 mL of ropivacaine 7.5 mg/mL on the 4 nerves (radial, median, ulnar, and musculocutaneous). Primary end point was the number of failed radial nerve sensory blocks at 30 mins. Results: The time to perform the block was not different between the 3 groups (17 mins [SD, 7 mins] vs 13 mins [SD, 8 mins] and 13 mins [SD, 4 mins], respectively). The time required to obtain a complete sensory block was shorter for the 4 nerves in group <0.5 mA, with a statistical significance for radial and musculocutaneous nerves in group <0.5 mA versus group 0.5-0.64 mA and group >0.65 mA. Patients in group <0.5 mA had a greater success rate for complete sensory radial nerve compared with those of group 0.5-0.64 mA and group >0.65 mA at any interval times between 5 and 30 mins ( P = 0.0001). Supplemental local anesthesia was provided for the 3 groups more frequently for the median nerve, with no difference between groups. Group >0.65 mA required 5 general anesthesias (20%) as compared with 1 (4%) in group <0.5 mA ( P < 0.05). No adverse event (dysesthesia) occurred after 48 hrs and 45 days. Conclusion: We conclude that intensity of stimulation influenced onset time and success rate.